The Vertical Hour - Hare, David, 1947- (Faber plays., 2008)
Nadia Blye is a young American war reporter turned academic who teaches Political Studies at Yale. A brief holiday with her boyfriend brings her into contact with a kind of Englishman whose culture and background are a surprise and a challenge both to her and to her relationship.